Interdisciplinary management of mpox-related local complications: report on a series of cases - Gamo Guerrero, María; Simón Gozalbo, Ana; Martín Díaz, Mariángeles; Díez Madueño, Kevin; Del Río Pena, Emilio; De la Cueva, Pablo; Talaván, Tamar; Jiménez, Eva; Torres, Juan; Valencia, Jorge; Cuevas, Guillermo; Bibiano, Carlos; et al. (Frontiers in Medicine, 2023)
Monkeypox (mpox) is a viral zoonosis, and human-to-human transmission can result from close contact with the respiratory secretions and mucocutaneous lesions of an infected person. The prodromal phase is followed by an eruptive phase, with skin and/or mucosal lesions that progress through several stages at different sites. In this study, we describe the importance of interdisciplinary care management and follow-up of patients with complicated mpox. A cross-sectional study was conducted from May 2022 until August 2022 at a secondary hospital in Madrid (Spain). Out of 100 patients with mpox seen at this institution, we selected and analyzed 11 with local complications. All the patients were male at birth, and the mean age was 32 (30-42) years. The clinical manifestations included skin rash or mucosal lesions, fever, myalgia and lymphadenopathies. The most frequent local complications were pharyngitis associated with dysphagia, penile edema, infection of the mucocutaneous lesions, and ulceration of the genital lesions. A multidisciplinary team was created for the care of patients with complications secondary to mpox. The team comprised dermatologists and specialists in infectious diseases, preventive medicine, and emergency medicine. This approach improved the ability to diagnose and treat early with supportive, topical, and systemic treatment. In our center most of the cases were self-limiting, and none were life-threatening. An interdisciplinary response to a public health alert enhances the management of complex patients and should be implemented in successive outbreaks of mpox.